2015
DOI: 10.1097/md.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Severe Paraquat Poisoning in an HIV-Positive Patient

Abstract: We described and analyzed the treatment process of an HIV-positive patient with severe paraquat (PQ) poisoning.A 34-year-old man ingested about 50 mL of a 20% solution of PQ in a suicide attempt. He was treated with gastric lavage, oral administration of adsorbent, and symptomatic treatments at the local hospital, and was transferred to our emergency department. Ten hours after the exposure, the concentration of plasma PQ was 2.17 mg/L and was substantially above the survival limits of the severity index for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The recovered HIV patients tended to suffer much less lung injury than the general PQpoisoned patients. In addition, they all had low CD4 + T lymphocyte levels due to HIV infection (RagoucySengler and Pileire, 1996;Shang and Lu, 2015;Tsai et al, 2016). These low counts of CD4 + T lymphocytes confirmed that the patients were in an immunosuppressed condition, which may be conducive to relieving the acute inflammation and lung fibrosis induced by PQ.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…The recovered HIV patients tended to suffer much less lung injury than the general PQpoisoned patients. In addition, they all had low CD4 + T lymphocyte levels due to HIV infection (RagoucySengler and Pileire, 1996;Shang and Lu, 2015;Tsai et al, 2016). These low counts of CD4 + T lymphocytes confirmed that the patients were in an immunosuppressed condition, which may be conducive to relieving the acute inflammation and lung fibrosis induced by PQ.…”
mentioning
confidence: 86%
“…This HIV-infected patient (with a serum concentration of 1.3 µg/ml PQ, five hours after exposure) survived after receiving lavage and diuresis, in spite of clinical and biological prognoses of death. Our team reported the second case of a 34-year-old man who had HIV infection and severe PQ poisoning (Shang and Lu, 2015). He survived with a good outcome despite a usually fatal serum concentration of PQ (2.17 µg/ml, ten hours after exposure) after receiving immunosuppressive therapy and HP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, it can simultaneously maintain electrolyte balance, control body temperature, and protect the liver and kidney. Moreover, resin HP has successfully treated some patients who have overdosed on highly lipid solubility drugs (Licari et al, 2009;Sikma et al, 2012;Zhang et al, 2012;Brandenburg et al, 2014;Shang and Lu, 2015). Such poisoning accidents were rare and are clinically critical, and it was difficult to perform a well-controlled study.…”
Section: Discussionmentioning
confidence: 99%
“…Paraquat poisoning-induced acute lung injury is thought to be associated with a strong and persistent inflammatory response Feng et al, 2018;Xu and Lu, 2019). Our group has reported that an acquired immune deficiency syndrome (AIDS) patient who ingested a lethal dose of paraquat had a good prognosis (Shang and Lu, 2015). Patients with AIDS are known to have immunodeficiency, whose immune system is suppressed, and that case could indirectly support the effectiveness of immunosuppressive therapy in treating patients with paraquat poisoning (Lu, 2018).…”
Section: Prospects For the Futurementioning
confidence: 99%